PERBANDINGAN PEMBERIAN HIDROTERAPI RENDAM KAKI AIR HANGAT DAN PIJAT AKUPRESUR TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI PRIMER - Nur Sella; Erwin Erwin; Riri Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Hypertension is a condition when the blood pressure rises chronically above 140/90 mmHg. Hypertension can cause stroke and coronary heart disease. Nonpharmacological therapy that can be used to lower the blood pressure is warm water feet-soaking hydrotherapy and acupressure. The purpose of this study was to compare warm water feet-soaking hydrotherapy and acupressure on the blood pressure in primary hypertension. This research used quasi experimental design with time series design approach. The research was conducted at PSTW Khusnul Khotimah Pekanbaru with 32 samples, divided into 16 intervention group I and 16 intervention group II with purposive sampling technique. The intervention group I was given warm water feet-soaking hydrotherapy for 15 minutes and the intervention group II was given an acupressure massage for 30 seconds. The measuring instrument is a digital sphygmomanometer and observation sheet. The analysis used was univariate analysis to see the frequency and percentage, and bivariate analysis with Wilcoxon Sign test and Mann Whitney test. The results showed the average lowering of systole and diastole blood pressure on intervention group I of 13.45 mmHg and 7.72 mmHg and the intervention group II of 6.5 mmHg and 2.49 mmHg. Statistical test results for intervals I and II showed mean difference of blood pressure systole with p value (0,033) < (0,05) and diastole with p value (0,038) < (0,05). The results showed that warm water feetsoaking hydrotherapy was more effective than acupressure massage to lower the blood pressure on primary hypertension patients.Keywords: Acupressure massage, Blood pressure Primary hypertension, warm water feet-soaking hydrotherapy,